Perencanaan Strategi SI/TI Pada Aplikasi Dana Menggunakan Metode SWOT Dan Perbandingan AHP - Aldiansyah Fathul Majid; Mochamad Bagus Okta Eka Pramuditya; Prind Triajeng Pungkasanti (Universitas Muhammadiyah Riau, 2024)
This research evaluates user satisfaction with the Dana application using a combination of two methods: SWOT analysis and utilizing one of the decision support system (DSS) methods using the Analytical Hierarchy Process (AHP) method. The SWOT method consists of strengths, weaknesses, opportunities, and threats. (Threats). The purpose of this research is to make the Dana application much better in the future. The main findings indicate that the majority of users show positive satisfaction with the service, supported by the highest rating in the Opportunities criterion in the SWOT analysis with a score of 2.329. This describes the potential of the Dana application to excel and grow in competition with competitors. In the context of AHP method evaluation, three main criteria were evaluated: application appearance, application features, and bank transfer on the Dana application. The evaluation of the application appearance yielded a score of 2.10 and an average rating of 3.16, indicating that most users are satisfied with the application interface. However, there is potential to improve the appearance aspect to better align with user preferences and needs. The application features received a score of 2.32 and an average rating of 3.02. These results show that most users are satisfied with the variety of features offered by the Dana application. Nevertheless, there is potential for improvement in certain features, and a deep understanding of user needs could be a primary focus to enhance customer satisfaction in this aspect. Bank transfer on the Dana application received a score of 2.35 with an average rating of 3.48. Overall, this research provides an understanding of customer satisfaction criteria on the Dana application and serves as a basis for developers to focus on further improvements and developments to achieve optimal satisfaction levels.